An Analysis of the Text Complexity of Leveled Passages in Four Popular Classroom Reading Assessments. Issue 3 (3rd July 2017) - Toyama, Yukie; Hiebert, Elfrieda H.; Pearson, P. David
ABSTRACT: This study investigated the complexity of leveled passages used in four classroom reading assessments. A total of 167 passages leveled for Grades 1–6 from these assessments were analyzed using four analytical tools of text complexity. More traditional, two-factor measures of text complexity found a general trend of fairly consistent across-grade progression of average complexity among the four assessments. However, considerable cross-assessment variability was observed in terms of the size of increase in complexity from grade to grade, the overall range of complexity, and the within-grade text complexity. These cross-assessment differences were less pronounced with newer, multi-factor analytical tools. The four assessments also differed in the extent to which their passages met the text complexity guidelines of the Common Core State Standards. The authors discuss implications of the differences found among and within the classroom assessment systems, on one hand, and among the measures of text complexity, on the other.